2006
DOI: 10.1523/jneurosci.1825-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Kv2.1 Potassium Channels Are Retained within Dynamic Cell Surface Microdomains That Are Defined by a Perimeter Fence

Abstract: Ion channel localization to specific cell surface regions is essential for proper neuronal function. The Kv2.1 K ϩ channel forms large clusters on the plasma membrane of hippocampal neurons and transfected human embryonic kidney (HEK) cells. Using live cell imaging, we address mechanisms underlying this Kv2.1 clustering in both HEK cells and cultured hippocampal neurons. The Kv2.1-containing surface clusters have properties unlike those expected for a scaffolding protein bound channel. After channel is deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
154
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(165 citation statements)
references
References 25 publications
11
154
0
Order By: Relevance
“…As previously described, Kv2.1 clusters are high-density structures containing most of the Kv2.1 expressed on the plasma membrane (8,13,14). Binding of various reagents to extracellular epitopes has confirmed that these structures are indeed on the cell surface (13).…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…As previously described, Kv2.1 clusters are high-density structures containing most of the Kv2.1 expressed on the plasma membrane (8,13,14). Binding of various reagents to extracellular epitopes has confirmed that these structures are indeed on the cell surface (13).…”
Section: Resultssupporting
confidence: 63%
“…It is noteworthy that the Kv2.1 expression levels and localization and the regulation of localization and function are nearly identical between transfected HEK cells and the endogenous Kv2.1 in cultured hippocampal neurons (8,9,(13)(14)(15). We report here that the clustered Kv2.1 is nonconducting and that the majority of the whole-cell current is derived from the nonclustered channels.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations